A serological and molecular survey of cattle hypodermosis in east-Turkey - Balkaya, Ibrahim; Simsek, Sami; Saki, Cem Ecmel (Elsevier Science Bv, 2010)
The aim of this study was to determine the seroprevalence of hypodermosis in cattle in East-Turkey and to identify Hypoderma species using morphological and molecular methods. For this purpose, a total of 778 serum samples of cattle were collected from Erzurum provinces of east-Turkey from December 2008 to February 2009. The sera were analyzed using a Hypodermin C antigen by means of indirect ELISA. In addition, 10 Hypoderma spp. larvae were collected from slaughtered animals in the abattoir for morphological identification and molecular characterization on the basis of mitochondrial CO1 gene sequence analysis and PCR-RFLP. Two hundred and twenty three (28.6%) out of 778 cattle were seropositive for hypoderma antibodies. All positive cattle were female of a local breed. Seven out of 10 Hypoderma larvae were morphologically classified as third instar larvae (L3) of H. bovis and 3 were classified as L3 of H. lineatum. The TaqI restriction enzyme was used to differentiate the Hypoderma species on the basis of the 438 and 250 bp bands for H. bovis and the 488 and 200 bp bands for H. lineatum resulting from PCR-RFLP. According to the alignment of the mitochondrial CO1 sequences of the Hypoderma species and the PCR-RFLP results, all examined larva samples were classified as H. bovis. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Hypoderma; Seroprevalance; ELISA; PCR-RFLP; Morphology